Optimization of Formulation Parameters in Preparation of Fructus ligustri lucidi Dropping Pills by Solid Dispersion Using 23 Full Experimental Design - Kai-Rong Wu; Wen-Ho Chuo; Yuh-Tyng Huang (MDPI AG, 2022)
Oleanolic acid (OA) is an active ingredient of the traditional Chinese medicine (TCM) Fructus ligustri lucidi (FLL). Its clinical use is restricted because it is water-insoluble and has limited dosage forms of administration at present. Hence, the FFL dropping pills were prepared by the hot-melt method of solid dispersion technology. A 23 factorial design was used to examine the effects of the materials used to prepare the dropping pills (e.g., different ratios of PEG4000 and PEG6000, FLL extract loading, and percentage of Tween 80) on parameters such as dropping pill roundness, weight variation, and disintegration time. Moreover, 23 full factorial design was utilized to search for the optimal formulation for dissolution experiments. The results showed that the percentage of Tween 80 demonstrated significant effects on dropping pill roundness, weight variation, and disintegration time; FLL extract loading affected roundness and weight variation; and different ratios of PEG4000 and PEG6000 only affected disintegration time. The optimal formulation of the dropping pills released 70% of the drug after 30 min of dissolution release, which was faster than commercially available FLL Chinese medicines. Furthermore, the amount released was higher than that of commercially available formulations. In this study, a solid dispersion technique was used to successfully produce FLL dropping pills. In addition to improving the water insolubility of FLL and increasing the dissolution release percentage of the drug, we increased the application value of FLL and reduced the issues of traditional administration dosage forms.